Pendampingan Pelaksanaan Proyek Penguatan Profil Pelajar Pancasila (P5) dengan Tema Kearifan Lokal - Kintoko, Kintoko; Rohmah, Lely Arbiati Nur; Warniasih, Kristina (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The Pancasila Student Profile is one of the efforts that is expected to improve the quality of education in Indonesia, one of which is by developing the character of students. Character development is very necessary for students to build highly intellectual people. The media used to develop student character is the implementation of the Pancasila Student Profile Strengthening Project. This service aims to provide insight and description of the implementation of the Strengthening Pancasila Student Profile (P5) Project with the theme of local wisdom in junior high schools to realize the implementation of the independent curriculum. This service activity method is carried out through observation and mentoring. The results of the activity show that students' knowledge about the local wisdom of traditional games in the surrounding area has increased and the moral character of students in junior high school can also be developed.